The Role of Parenting in the Formation of the Character of the Assalam Islamic Boarding School - Ismail, Ismail; Suroso, Suroso; Sayid Habiburrahman; Hoirul Amri; Zuhri, Syarifuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Education plays a fundamental role in shaping human personality, especially character development through a planned and continuous process. This study aims to analyze the role of character education and parenting in shaping the personality of students in a pesantren environment. Using a descriptive qualitative approach, data were collected through participatory observation for 3 months, in-depth interviews with 15 santri, 5 caregivers, and 3 kyai, as well as analysis of curriculum documents and daily records. The findings show that consistent parenting patterns through the example set by the clerics (80% of students imitate positive behavior), the habit of worship such as daily tahajud and weekly muhadharah, and hirz discipline (strict supervision) contribute significantly to student character. Specifically, religious attitudes increased from 65% to 92% (behavioral observation), morals were nurtured with a 40% decrease in violations in 6 months, and social behavior improved through tahfidz group collaboration (75% active participation). These results confirm the integration of character education with systematic parenting as the key to optimizing students' personalities. The study's conclusion recommends replicating this model in other Islamic boarding schools to strengthen Islamic-based character.